Pharmacophore modeling and molecular docking of phytoconstituents in Morus sp. and Arcangelisia flava against nitric oxide synthase for antiinflammatory discovery - Jutti Levita, Recky Patala&, Jennifer Kolina, Tiana Milanda, Mutakin Mutakin, Irma Melyani Puspitasari, Nyi Mekar Saptarini, Sri Adi Sumiwi (Journal of Applied Pharmaceutical Science, 2018)
Objective: To discover inducible nitric oxide synthase (iNOS) inhibitors from Morus sp. and Arcangelisia flava for anti-inflammatory drug candidates. Methods: The protein crystal structures of human iNOS in complex with AT2 (PDB code: 3E7G) and S-ethylisothiourea (SEITU) (PDB code: 4NOS) were selected, their ligand-protein interaction was studied by employing LigandScout to obtain the pharmacophore features, which were validated against iNOS database and the result was used to screen the pharmacophores of 29 phytoconstituents in Morus sp. and A. flava. Molecular docking of the phytoconstituents into iNOS binding pocket was performed using AutoDock 4.2.6. Results: The pharmacophore features obtained were one aromatic ring, one hydrogen bond donor, and one hydrogen bond acceptor, which were proved valid against iNOS training set (GH score = 0.80; AUC100% ROC curve = 0.64 for AT2 and GH score = 0.73; AUC100% ROC curve = 0.65). Ten phytoconstituents in A. flava and eight compounds in Morus sp. interact with Glu377, an important amino acid residue in iNOS binding pocket. Sanggenon F of Morus sp. indicates the best affinity (docking score—9.88 kcal/mol, respectively), compared with that of SEITU (docking score—5.48 kcal/mol). Conclusions: Phytoconstituents in Morus sp. and A. flava fit the pharmacophore features generated from AT2 or SEITU complex with iNOS, therefore, they might be potential as iNOS inhibitors. Of 29 phytoconstituents, sanggenon F in Morus sp. indicates the best the docking score. Its score is better than SEITU, a known iNOS inhibitor.
Keywords: Arcangelisia flava, humaniNOS, inflammation, Morussp., nitric oxide synthase,yellow root.